Removal of disperse dye from alcoholysis products of waste PET fabrics by nitric acid-modified activated carbon as an adsorbent: Kinetic and thermodynamic studies. Issue 17 (September 2020) - Li, Mengjuan; Lu, Jing; Li, Xiaoqiang; Ge, Mingqiao; Li, Yonggui
Decolorization technology is a critical problem of high-quality chemical recycling and recovery of waste poly(ethylene terephthalate) (PET) textiles. In order to deal with this problem, nitric acid-modified activated carbon (AC-HNO3 ) was utilized as an adsorbent for removal of C.I. Disperse Red 60 (DR60) from the glycolysis products of waste PET fabrics. The glycolysis product was bis(2-hydroxyethyl) terephthalate (BHET). The pore structure and surface properties of AC and AC-HNO3 samples were characterized by N2 adsorption, differential thermogravimetric analysis (DTG) and elemental analyses (EA). Modification with nitric acid increased the amount of oxygen groups of the activated carbon from 12.3% to 18.0% and enhanced the electrostatic attraction between dye molecules and activated carbon. The average color removal ratio of DR60 on AC-HNO3 increased into 97.6 ± 0.5%, which is better than that on raw AC (85.0 ± 1.6%). Relative whiteness of BHET increased from 40.3 ± 0.9% to 98.3 ± 1.1%. The adsorption kinetics for DR60 on the AC-HNO3 were studied using pseudo-first order and pseudo-second order models and fitted to the latter well ( R 2  = 0.9999). To investigate the adsorption equilibrium behavior, Freundlich and Langmuir models were examined. The results showed that the Langmuir model provided better correlation ( q max  = 163.9 mg/g). The adsorption isotherms at different temperatures were used for the determination of thermodynamic parameters. Based on the data of Δ G 0, Δ H 0 and E a, the adsorption process was physisorption.